PENDEKATAN SEJARAH KAJIAN HADITS-HADITS TARAWIH - Nurma Ali Ridlwan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2012)
The number of rakaat of shalat tarawih performed by Muslims in Indonesia tends to be acontroversion leading to conflicts among them. A group of Muslims prefer to do this prayerseparately from the other group that perform this prayer in different number of rakaat.In some cases, there are more serious conflich in which a group of Muslims forbid othergroup to perform this prayer in their mosque because of their different number of rakaat. In sucha case, claim of truth is more dominant than the spirit of Islamic teaching, in this case shalattarawih, as a means of consolidating the various types of Islamic preaching.This article describes some hadits related to shalat tarawih with historical perspective inorder to see it in harmony with the society and its culture. This approach is aimed at understandhadits comprehensively.